Physical Activity in Long-term Survivors of Acute Lymphoblastic Leukemia in Childhood and Adolescence: A Cross-sectional Cohort Study. Issue 1 (January 2017) - Nayiager, Trishana; Barr, Ronald D.; Anderson, Loretta; Cranston, Amy; Hay, John
Abstract : Inadequate physical activity (PA) and elevated overweight/obesity (OW/OB) rates are common in survivors of cancer in childhood, especially acute lymphoblastic leukemia (ALL). Bony morbidity, including fractures, is also prevalent among survivors of ALL. This study examined the interrelationships of PA, measured in hours by the Habitual Activity Estimation Scale; OW/OG, defined by body mass index; and fractures (yes/no) in survivors of ALL (n=75) more than 10 years after diagnosis. All had been treated using protocols of the Dana Farber Cancer Institute Childhood ALL Consortium. The median age was 21.15 years and time from diagnosis 15.07 years, and 27 subjects had experienced fractures. More than 30% of the total sample were OW/OB. There was no correlation of body mass index with present PA. There were no significant differences between those with/without fractures in terms of age, sex, time from diagnosis, and the prevalence of OW/OB. Subjects with fractures during treatment reported more total activity on typical weekend days than those without fractures (mean 8.8 vs. 6.9 h, P <0.01). There was no significant difference on weekdays. Higher activity on weekends suggests that fractures may have occurred more commonly in those who had a more active lifestyle before, during, and after treatment.